Differential control of CD4+ T‐cell subsets by the PD‐1/PD‐L1 axis in a mouse model of allergic asthma. Issue 4 (26th February 2015) - McAlees, Jaclyn W.; Lajoie, Stephane; Dienger, Krista; Sproles, Alyssa A.; Richgels, Phoebe K.; Yang, Yanfen; Khodoun, Marat; Azuma, Miyuki; Yagita, Hideo; Fulkerson, Patricia C.; Wills‐Karp, Marsha; Lewkowich, Ian P.
<x xml:space="preserve">Abstract</x> Studies examining the role of PD‐1 family members in allergic asthma have yielded conflicting results. Using a mouse model of allergic asthma, we demonstrate that blockade of PD‐1/PD‐L1 has distinct influences on different CD4+ T‐cell subsets. PD‐1/PD‐L1 blockade enhances airway hyperreactivity (AHR), not by altering the magnitude of the underlying Th2‐type immune response, but by allowing the development of a concomitant Th17‐type immune response. Supporting differential CD4+ T‐cell responsiveness to PD‐1‐mediated inhibition, naïve PD‐1−/− mice displayed elevated Th1 and Th17 levels, but diminished Th2 cytokine levels, and ligation of PD‐1 in WT cells limited cytokine production by in vitro polarized Th1 and Th17 cells, but slightly enhanced cytokine production by in vitro polarized Th2 cells. Furthermore, PD‐1 ligation enhanced Th2 cytokine production by naïve T cells cultured under nonpolarizing conditions. These data demonstrate that different CD4+ T‐cell subsets respond differentially to PD‐1 ligation and may explain some of the variable results observed in control of allergic asthma by the PD‐1 family members. As the PD‐1/PD‐L1 axis limits asthma severity by constraining Th17 cell activity, this suggests that severe allergic asthma may be associated with a defective PD‐1/PD‐L1 regulatory axis in some individuals.